Mating game : a primer on love, sex and marriage, The - Regan, Pamela (California : Sage Publications, 2003)
Contenido: Love: general theories of love. Passionate and companionate love. Love gone bad: problematic. Sexual attitudes. Sexuality in beginning relationships. Sex gone bad: problematic. Aspects of relational sexuality. Mate selection and marriage: general theories of mate selection. Mate preferences. Attraction and courtship. Relationship development. Conflict and dissolution. Marriage. Individual differences. Maleness and femaleness. Personality. Interpersonal belief systems. Concluding remarks.